Mineral magnetism variables as potential indicators of permafrost aggradation and degradation at the southern edge of the permafrost zone, Northeast China. (12th January 2021) - Zhu, Chenyi; Wang, Hongya; Li, Shuai; Luo, Yao; Xue, Tianyi; Song, Yaqiong; Qiu, An'an; Liu, Hongyan
Abstract : The northern Greater Khingan Range is located in northernmost Northeast China on the southern edge of the permafrost zone of the Northern Hemisphere. Isolated, sporadic and continuous permafrost belts are distributed from the southeast to the northwest in this area. Sixteen surface soil samples were collected from the three permafrost belts, and a 30‐cm‐deep soil profile was sampled from the continuous permafrost belt. A 70‐cm‐long sediment core was recovered from a small lake in the continuous permafrost belt. Measurements of mineral magnetism and analysis of total organic carbon (TOC) and total nitrogen (TN) were performed on the soil samples, while mineral magnetism measurements, pollen analysis and accelerator mass spectrometry (AMS) 14 C dating were made on the lake sediment samples. The purpose was to explore whether the mineral magnetism of the soils and sediments in combination with TOC, C/N and pollen data would be indicative of recent and past permafrost alterations. Stable single domain (SSD) ferrimagnets were rarer in relative and/or absolute terms in the surficial isolated‐sporadic permafrost and the upper horizons of the soil profile, suggesting stronger gleization and thawing. The variations in TOC and C/N support these inferences. Temporal changes in mineral magnetism of the sediment core indicate varying pedogenesis and gleization and permafrost aggradations and degradations in the catchment and shifts of the permafrost belts over the past ~1000 years. The reconstructed permafrost alterations attributable to local climate changes suggested by the pollen data can be related to northern hemispheric and regional climate changes in the past ~1000 years and are helpful for predicting migrations of the permafrost belts in the future.